The consequences of trade union power erosion - John T. Addison (IZA World of Labor, 2014)
The micro- and macroeconomic effects of the declining power of trade unions have been hotly debated by economists and policymakers. Nevertheless, the empirical evidence shows that the impact of the decline on economic aggregates and firm performance is not an overwhelming cause for concern. However, the association of declining union power with rising earnings inequality and a loss of direct communication between workers and firms is potentially more worrisome. This in turn raises the questions of how supportive contemporary unionism is of wage solidarity, and whether the depiction of the nonunion workplace as an authoritarian “bleak house” is more caricature than reality.
Keywords: J30; J38; J41; J51; J53; J58; 330; union density/coverage; bargaining structure; coordination; macro/micro performance; redistribution; voice